A glycoprotein subunit vaccine elicits a strong Rift Valley fever virus neutralizing antibody response in sheep - Faburay, Bonto; Lebedev, Maxim; McVey, D. Scott; Wilson, William C.; Morozov, Igor; Young, Alan; Richt, Juergen A. (My University, 2015)
Rift Valley fever virus (RVFV), a member of the Bunyaviridae family, is a mosquito-borne zoonotic pathogen that causes serious morbidity and mortality in livestock and humans. The recent spread of the virus beyond its traditional endemic boundaries in Africa to the Arabian Peninsula coupled with the presence of susceptible vectors in non-endemic countries has created increased interest in RVF vaccines. Subunit vaccines composed of specific virus proteins expressed in eukaryotic or prokaryotic expression systems are shown to elicit neutralizing antibodies in susceptible hosts. RVFV structural proteins, N-terminus glycoprotein (Gn) and C-terminus glycoprotein (Gc), were expressed using a recombinant baculovirus expression system. The recombinant proteins were reconstituted as GnGc subunit vaccine formulation and evaluated for immunogenicity in a target species, sheep. Six sheep were each immunized with a primary dose of 50 μg of each vaccine immunogen adjuvanted with montanide ISA25, and at day 21 post-vaccination, each animal received a second dose of the same vaccine. The vaccine induced strong antibody response in all animals as determined by indirect enzyme-linked immunosorbent assay (ELISA). Plaque reduction neutralization test (PRNT80) showed the primary dose of the vaccine was sufficient to elicit potentially protective virus neutralizing antibody titers ranging from 40 to 160, and the second vaccine dose boosted the titer to more than 1,280. Further, all animals tested positive for neutralizing antibodies at day 328 pv. ELISA analysis using the recombinant nucleocapsid protein as a negative marker antigen indicated that the vaccine candidate is DIVA (differentiating infected from vaccinated animals) compatible, and represents a promising vaccine platform for RVFV infection in susceptible species.
Keywords: Rift Valley fever virus; Glycoproteins; Subunit vaccine; Neutralizing antibodies; Sheep